Efficient Multi-Stage Conjugate Gradient for Trust Region Step - Gong, Pinghua; Zhang, Changshui (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
The trust region step problem, by solving a sphere constrained quadratic programming, plays a critical role in the trust region Newton method. In this paper, we propose an efficient Multi-Stage Conjugate Gradient (MSCG) algorithm to compute the trust region step in a multi-stage manner. Specifically, when the iterative solution is in the interior of the sphere, we perform the conjugate gradient procedure. Otherwise, we perform a gradient descent procedure which points to the inner of the sphere and can make the next iterative solution be a interior point. Subsequently, we proceed with the conjugate gradient procedure again. We repeat the above procedures until convergence. We also present a theoretical analysis which shows that the MSCG algorithm converges. Moreover, the proposed MSCG algorithm can generate a solution in any prescribed precision controlled by a tolerance parameter which is the only parameter we need. Experimental results on large-scale text data sets demonstrate our proposed MSCG algorithm has a faster convergence speed compared with the state-of-the-art algorithms.